Species' attributes predict the relative magnitude of ecological and genetic recovery following mass mortality. Issue 22 (17th October 2022) - Schiebelhut, Lauren M.; Gaylord, Brian; Grosberg, Richard K.; Jurgens, Laura J.; Dawson, Michael N.
Abstract: Theoretically, species' characteristics should allow estimation of dispersal potential and, in turn, explain levels of population genetic differentiation. However, a mismatch between traits and genetic patterns is often reported for marine species, and interpreted as evidence that life‐history traits do not influence dispersal. Here, we couple ecological and genomic methods to test the hypothesis that species with attributes favouring greater dispersal potential—e.g., longer pelagic duration, higher fecundity and larger population size—have greater realized dispersal overall. We used a natural experiment created by a large‐scale and multispecies mortality event which created a "clean slate" on which to study recruitment dynamics, thus simplifying a usually complex problem. We surveyed four species of differing dispersal potential to quantify the abundance and distribution of recruits and to genetically assign these recruits to probable parental sources. Species with higher dispersal potential recolonized a broader extent of the impacted range, did so more quickly and recovered more genetic diversity than species with lower dispersal potential. Moreover, populations of taxa with higher dispersal potential exhibited more immigration (71%–92% of recruits) than taxa with lower dispersal potential (17%–44% of recruits). By linking ecological with genomic perspectives, we demonstrate that a suite of interacting life‐history and demographic attributes do influence species' realized dispersal and genetic neighbourhoods. To better understand species' resilience and recovery in this time of global change, integrative eco‐evolutionary approaches are needed to more rigorously evaluate the effect of dispersal‐linked attributes on realized dispersal and population genetic differentiation.